Methylenetetrahydrofolate reductase gene polymorphisms, lipid profiles, and basic renal functional markers as risk for myocardial infarction: a case-control study and haplotype analysis - Perović, Svetlana; Vujović, Slavica; Kapur Pojskić, Lejla; Garai, Nemanja; Šćepanović, Anđelka (Archives of Biological Sciences, 2024)
Paper description: The interplay of genetic and environmental factors causes myocardial infarction (MI), characterized by gradual worsening of atherosclerosis. The association of methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C gene variants and different haplotypes, and the risk of MI were examined in the Montenegrin population. The MTHFR C677T polymorphism is associated with a higher risk of MI (P=0.006) and the A-T haplotype (P=0.004). C677T and A1298C MTHFR polymorphisms are associated with elevated creatinine levels in MI patients (P=0.003 and P=0.002, respectively). The MTHFR C677T polymorphism is associated with MI and is a potential genetic risk factor. Abstract: Myocardial infarction (MI) is a serious cardiovascular disease and the primary cause of mortality, with a complex etiopathology. Identifying the genetic basis of myocardial infarction (MI) is essential for developing personalized medical treatments. This study examined the possible association between polymorphisms in the methylenetetrahydrofolate reductase (MTHFR) gene and MI. In the study, 120 patients with MI and 120 age-and-sex-matched controls were genotyped for C677T and A1298C MTHFR polymorphisms by the allele-specific or amplification refractory mutation system-polymerase chain reaction (ARMS-PCR). In the case of the C677T polymorphism, the T/T and C/T genotypes were associated with a significantly increased risk of MI under the dominant genetic model (odds ratio (OR)=2.060; P=0.006). Although there was no significant association between the A1298C variant and MI, this polymorphism was linked to a higher level of creatinine in MI patients (P<0.002). A similar association was observed for the C677T polymorphism (P=0.003). An A-T haplotype represented an increased risk for MI (OR=1.630; P=0.014), whereas the A-C haplotype had a protective role (R=0.517; P=0.002). These findings indicate that C677T MTHFR polymorphism is strongly associated with and increased risk of MI, making it a potential genetic risk factor and a possible predictor of MI.